URGENSI BIMBINGAN KELUARGA SAKINAH BAGI KETAHANAN KELUARGA DITINJAU DARI HUKUM ISLAM - Aby Abdillah Ibnu Yahya; Patimah Patimah; Muhammad Fajri (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2023)
This thesis discusses the urgency of guidance for the sakinah family at the Office of Religious Affairs in terms of Islamic Law at the Office of Religious Affairs, Manggala District. With the main problem, how is the urgency of sakinah family guidance for family resilience in terms of Islamic law and how is the implementation of sakinah family guidance in the Office of Religious Affairs, Manggala District. This type of research is a qualitative research using a normative approach to Islamic law, juridical. The data sources of this study are primary and secondary data sources, then for the data collection methods sourced from primary data in the form of direct interviews and documentation. This research was conducted at the Office of Religious Affairs, Manggala District, with the results of the study that it is mandatory for each KUA to apply Sakinah Family Guidance which aims to make brides and grooms know more about the basics of dealing with and fostering a household so as to minimize divorce rates and domestic violence. The scholars have also agreed that the formation of the law for the benefit of this ummah has created good and avoided evil. and the implementation of this guidance received a positive response from the bimwin participants because they had presented the main materials and had also tried their best in implementing bimwin to the community. Suggestions from the author It is necessary to have awareness and attention from the Government and the community about the importance of implementing sakinah family guidance for family resilience in the community in order to minimize the divorce that occurs.